Silica‐Coated Gold Nanorod Supraparticles: A Tunable Platform for Surface Enhanced Raman Spectroscopy. (10th April 2022) - van der Hoeven, Jessi E.S.; Gurunarayanan, Harith; Bransen, Maarten; de Winter, D.A. Matthijs; de Jongh, Petra E.; van Blaaderen, Alfons
Abstract: Plasmonic nanoparticle assemblies are promising functional materials for surface‐enhanced Raman spectroscopy (SERS). Gold nanorod (AuNR) assemblies are of particular interest due to the large, shape‐induced local field enhancement and the tunable surface plasmon resonance of the AuNRs. Designing the optimal assembly structure for SERS, however, is challenging and requires a delicate balance between the interparticle distance, porosity, and wetting of the assembly. Here, a new type of functional assemblies–called supraparticles–fabricated through the solvent‐evaporation driven assembly of silica‐coated gold nanorods into spherical ensembles, in which the plasmonic coupling and the mass transport is tuned through the thickness and porosity of the silica shells are introduced. Etching of the AuNRs allowed fine‐tuning of the plasmonic response to the laser excitation wavelength. Using a correlative SERS‐electron microscopy approach, it is shown that all supraparticles successfully amplified the Raman signal of the crystal violet probe molecules, and that the Raman signal strongly increased when decreasing the silica shell thickness from 35 to 3 nm, provided that the supraparticles have a sufficiently high porosity. The supraparticles introduced in this study present a novel class of materials for sensing, and open up a wide parameter space to optimize their performance. Abstract : Supraparticles are a new type of functional assemblies for surface‐enhanced Raman spectroscopy fabricated through the solvent‐evaporation driven assembly of silica‐coated gold nanorods. The plasmonic coupling and the mass transport in these spherical assemblies is tuned through the thickness and porosity of the silica shells, and through the gold nanorod core size.